Γ‐Oryzanol concentrations in various rice genotypes ripened under different air temperatures. Issue 6 (5th September 2022) - Nakano, Hiroshi; Yoshida, Hiroe; Yabe, Shiori; Fushimi, Erina; Tanaka, Ryo; Yamasaki, Masanori; Nakagawa, Hiroshi
Abstract: Background and Objective: Two steryl ferulates (γ‐oryzanol), that is, cycloartenyl ferulate and 24‐methylenecycloartanyl ferulate, were previously isolated as biomarkers for heat stress during ripening in rice ( Oryza sativa L.). γ‐Oryzanol is also known to exert several biomedical effects, such as antihyperlipidemic, antidiabetic, anti‐inflammatory, and anticancer activities. In the present study, we aimed to determine the effect of air temperature during 1–30, 1–15, and 16–30 days after heading on the concentrations of γ‐oryzanol using 92 rice genotypes. Findings: The concentration of cycloartenyl ferulate had strong negative correlations with daily maximum air temperatures during 16–30 days after heading. However, the concentrations of 24‐methylenecycloartanyl ferulate and total γ‐oryzanol exhibited strong positive correlations with daily minimum air temperatures during 1–15 days after heading. Moreover, there were strong genotypic differences in the concentrations of these compounds. Conclusion: The concentrations of cycloartenyl ferulate, 24‐methylenecycloartanyl ferulate, and total γ‐oryzanol can be modulated by the selection of cultivars and growing seasons. Significance and Novelty: This study investigates the concentrations of cycloartenyl ferulate, 24‐methylenecycloartanyl ferulate, and total γ‐oryzanol in 92 rice genotypes ripened under different air temperatures, which provided essential information for the development of rice cultivars and farming methods modulating γ‐oryzanol concentration.